GPS spoofing and anti-spoofing - Thiam, Wenzhi (Nanyang Technological University, 2023)
With the proliferation of digital transformation in the 21st century, there has been an exponential increase in the reliance on Global Navigation Satellite Systems (GNSS) such as the use of Global Positioning System (GPS) in our day to day lives. While these services have brought about a great amount of convenience, it is by far a secure service. Since position and time data of mobile devices are often treated as legitimate by default, this provides a huge attack vector for malicious actors. GNSS spoofing is one type of attack that malicious actors can take advantage of given the ease of conducting said attack. GNSS spoofing refers to an attempt by malicious attackers to deceive GNSS receivers into decoding an incorrect position, velocity and time (PVT). This final year project focuses on showing the susceptibility of modern-day mobile phones to GNSS spoofing using an open-source code and a Software-Defined Radio (SDR) while also providing some suggestions on increasing positioning security during the development of mobile devices.